A Comparative Study of Science Learning Motivation Between Students in Senior High Schools and Madrasah Aliyah - Pranata, Ogi Danika; Sari, Salsabila Dwita Febri; Ajani, Syairifah Mila; Putri, Nazila Wilia (Al Kawnu : Science and Local Wisdom Journal, 2025)
The success of science learning depends largely on students' motivation. The purpose of this study is to describe students' motivation to learn science and to compare the levels of motivation between students at a public high school (SMA) and a public Islamic high school (MA) in Sungai Penuh. A descriptive and comparative quantitative approach was used to collect data from 68 11th-grade science students using the validated Students' Motivation Toward Science Learning (SMTSL) instrument. The sample included all eleventh-grade science students from both schools, for a total of 36 SMA students and 32 MA students. Descriptive statistics revealed that the students were motivated to learn science (Mean = 3.58), with the highest scores on the active learning strategies scale. A comparative analysis using an independent samples t-test revealed that SMA students were significantly more motivated than MA students on two scales: science learning value and performance goal. The difference in the value of science learning was particularly evident in how students perceived science as a means of satisfying curiosity, solving problems, and relating to daily life. Meanwhile, some MA students demonstrated extrinsic motivation, such as gaining attention. These findings underscore the importance of fostering intrinsic motivation and meaningful engagement in science learning across different school types to promote equitable educational outcomes in science.